KETERLIBATAN ORANG TUA DALAM MENGEMBANGKAN MINAT MEMBACA ANAK USIA PRASEKOLAH - Utami, Nadia Rahma; Kurniawati, Farida (Universitas Negeri Jakarta, 2022)
This research was conducted to find out how parents can be involved in developing reading interest in preschoolers. In this study, parental involvement is seen as parental participation in every child's activity to develop children's reading interest. The research method used is a systematic literature review by collecting articles related to the research theme through the EBSCOhost and ScienceDirect databases published between 2012-2021. After extraction, three articles (n=3) met the specified criteria. Data analysis was carried out by synthetic analysis in a narrative manner. The results of the study show that parental involvement in developing children's reading interests can be done through sharing books and reading with children, but not just reading together, there are strategies that can be applied such as dialogic reading techniques. Parents can be involved in developing children's reading interests after being given guidance on reading activities with children at home and resources in the form of reading books to be used with children. The limitations of the study and recommendations for further research are discussed in the last section.